PRINSIP-PRINSIP GOOD GOVERNANCE DALAM PELAYANAN PUBLIK DI KANTOR CAMAT KORMOMOLIN KABUPATEN MALUKU TENGGARA BARAT - DUARMAS, DARMANERUS; Rumapea, Patar; ROMPAS, WELSON YAPPI (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT : Implementation of good governance is an absolute necessity for the creation of a majorityof the political system of governance that is more aligned to the interests of the people in accordance withthe principles of democracy are universal. The purpose of this study is to investigate the implementationof the principles of good governance in the public service, to determine the factors supporting andhindering the implementation of the principles of good governance in the public service in the District ofWest Southeast Maluku District Kormomolin.The method used in this research is quantitative method. Research was carried by 75 votes kormomolinsub-district government officials and the public. The data used are primary data in the can through aquestionnaire. The analysis technique used to test the hypothesis is simple linear regression analysis.The results of data analysis showed that the variables of good governance and positive significant effect onthe variable public services at the level of 95%. Based on the results of that study concluded that goodgovernance positive and significant impact on public services at Head Office Kormomolin.It is recommended that the implementation of good governance which emphasizes the principles oftransparency and accountability in Head Office Kormomolin should be increased for the realization ofpublic services from the aspect of efficiency and effectiveness.Keywords: good governance, public services